Visual Health Assessment and evaluation of Anthropogenic threats to Arabian Sea Humpback Whales in Oman - Minton, Gianna; Van Bressem, Marie Francoise; Willson, Andrew; Collins, Timothy; Al Harthi, Suaad; Sarrouf Willson, Maia; Baldwin, Robert; Leslie, Matthew; Van Waerebeek, Koen (J. Cetacean Res. Manage., 2022)
The sub-population of humpback whales inhabiting the Arabian Sea is a small and genetically distinct population that remains in low latitudes year round. Designated as Endangered on the IUCN Red list of Threatened Species, the population faces a number of threats throughout its range, including entanglement in fishing gear, ship strikes, and habitat degradation. Research conducted primarily off the coast of Oman over the past 20 years has contributed to understanding the population’s distribution, abundance, and conservation status. However information on the population’s health and specific threats is limited. This study examines all available images of Arabian Sea humpback whales obtained between 2000 and 2018 for evidence of disease, predation, epizoites and human-induced scarring or injury to individuals. Tattoo-like skin disease was detected in 43.4% of 83 adult whales, with a roughly equal distribution between males and females. Prevalence of the disease was significantly higher in 2012-2018 (51.7%) than in 2000-2011 (24.1%). Killer whale tooth rakes were detected on the ventral surface of the tail flukes of 12% (95% CI 4.5-18%) of 77 individuals. Roughly two thirds (66.6%: 95% CI 52-80%) of the 42 individuals represented by good quality photos of the caudal peduncle region at the fluke insertion bore scarring patterns consistent with entanglement in fishing gear. Four individuals had injuries consistent with vessel strikes and at least two other individuals showed severe injuries and deformations likely caused by interactions with fishing gear. Documented entanglement events from Oman and Pakistan involved large-mesh nylon gillnets, known to be used extensively throughout the Arabian Sea. These findings indicate an urgent need to design effective management and mitigation of threats, and to continue monitoring Arabian Sea humpback whales, with an emphasis on methods that allow continued and expanded assessment of health, body condition, and anthropogenic interactions.